The Meaning of The Lilian Tradition as Communication of Local Wisdom in Human Civilization - Lisda Ariani Simabur (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Local wisdom in the form of the cooperation tradition is important in human civilization. Communication in the gotong royong can strengthen social relations, build solidarity, and promote togetherness in society. One of the surviving cooperation traditions is Lilian. The Lilian tradition is still maintained and preserved by the people of North Maluku who live in Ternate as a form of cooperation and local wisdom communication in today's human civilization. The research objective is to achieve the meaning of the Lilian tradition as a communication of local wisdom in cooperation in human civilization among the people of the city of Ternate. The research method used is a qualitative method with a descriptive approach. The results of the research conclusions show that; The meaning of the Lilian Tradition can be interpreted as having the nature of helping each other, a sense of initiative, togetherness, and always maintaining communication when sitting together while carrying out Lilian activities. The Lilian tradition is a tradition that always colors the lives of the people of North Maluku in the city of Ternate in realizing the concept of social interaction. Besides that, Lilian's concept has been known for many years from their ancestors until now. So Lilian is a concept that will resolve the burden borne by people who carry out celebrations or suffer calamities but are borne together and resolved jointly by the local community.